Caffeine placebo effect in sport and exercise: A systematic review - Vega-Muñoz. A.; Contreras-Barraza, N.; Salazar-Sepúlveda, G.; Lay, N.; Gil-Marín, M.; Muñoz-Urtubia, N. (Nutrients, 2024)
The objective of this review article is to systematically identify the caffeine placebo effect in sport and exercise activities. We selected randomized controlled trial studies to better understand the impact of caffeine and its placebo effect on sports performance. We extracted a set of articles that refer strictly to the topics of caffeine and its placebo effect in sport and exercise, considering the databases integrated to the Core Collection Web of Science and Scopus, as well as the registration of the documents in PubMed®, a system with a selection process aligned with the guidelines for the PRISMA methodology, establishing the eligibility criteria of the articles with the PICOS tool, to which a systematic review is applied. Finally, the results show that caffeine improves anaerobic capacity and endurance, while placebo perceived as caffeine can also increase performance by reducing pain and improving concentration. This finding underscores the influence of expectations and placebo on physical performance, suggesting that managing these expectations may be an effective strategy for improving athletic performance.